La tercera caída de Constantinopla - Castillo Didier, Miguel (Byzantion Nea Hellás, 2015)
The yearly chant of the hymn Ti Hipermajo Stratigó ta Nikitiria at the Church of the Virgin of Blachernae, together with the visit of Constantinople's few Greeks inhabitants to the ayiásmata of Blachernae and of Zoodojos Piyí Monastery, constitute the already dying continuation of traditions which go back to the 7th century. They are a remain of living and flourishing traditions which persisted after 1453 until the Third Fall of Constantinople, term which has been used to refer to the process of systematic annihilation of Constantinopolitan Hellenism, which began in 1923, reached its peak with the progrom during the evening and night between September 6th and 7th of 1955, and has attained almost completion with the massive expulsion of Greeks during the decade of 1960.